Effects of selected herbal extracts on sexual maturity, growth performance and immune response of nile tilapia (Oreochromis niloticus Linnaeus) - Kareem, Zana Hama Gharib (2015)
Precocious puberty is a serious problem, which prevents fish from reaching its full aquaculture potential and is regarded as a limitation to the Nile tilapia farming. Delaying sexual maturity of Nile tilapia is crucial in order to control the number of unwanted fish in the pond leading to solving the overcrowding, food shortage, diseases and growth problems. The aim of this study was to investigate the effect of four screened herbs extracts (Neem leaves (Azadirachta indica), Asthma weed (Euphorbia hirta), Papaya seed (Carica. papaya) and Camphor bark (Cinnamomum camphora)) on the sexual maturity, growth performance and immune response of Nile tilapia. Thus a 90 days feeding trial (experiment I) was conducted on gonado/somatic index (GSI), histopathological examination of the gonads (as an indication of gonadal development), growth performance, feeding efficacy, body indices (hepato/ somatic index (HSI), spleeno/somatic index (SSI), blood parameters as an indication of immune response of Nile tilapia. In this experiment the fish fed ad libitum on diets supplemented with different crude plant extracts from C. camphora, E. hirta, A. indica, and C. papaya at 2 g /kg diet and a control diet. This experiment was followed by a 14 days challenge test (experiment II) with a virulent Gram+ve bacterial strain of Streptococcus agalactiae. All treatments and control group were triplicated and each treatment consisted of 30 fish (Total body weight of 90-110 g and Total Length of 18-20 cm). The most effective herbal extract according to results of experiments I and II, which was C. papaya, was selected and applied in experiment III in a different doses (0.5, 1, 2 g/kg diet) and two different periods of feeding (3 and 20 weeks) on 420 sac-larvae (3 days old) of Nile tilapia with initial weight of 0.015 g and total length of 9.43 mm. The sac-larvae were equally and randomly distributed into 21 glass tanks (20 sac-larvae/ aquarium). Results of this study showed that C. papaya extract 2 g/kg diet was the most effective herb on delaying gonadal development and sexual maturity in both males and females Nile tilapia. C. papaya extracts as well as significantly increased the growth performance it did not affect the immune response of Nile tilapia. Similarly, dietary A. indica was significantly reduced the GSI of the fish, but it had no effect on growth performance and it had negative effect on immune response, as evidenced by significantly lower and higher HSI and plasma alanine aminotransferase ALT, respectively. The diet supplemented with C. camphora and E. hirta, extracts also significantly improved the growth performance of Nile tilapia. While, the extracts of C. camphora and E. hirta were not significantly differed the sexual maturity of fish when compared with control group. Further, crude body lipid was lower in fish fed on the diet supplemented with C. camphora, E. hirta and C. papaya treatments, but was only significantly lower for the E. hirta treatment compared to the control. The results of experiment II showed that after 14 days of bacterial challenge, Nile tilapia fed on C. camphora extract supplementation had significantly higher survival rate and relative percent survival (RPS), compared to the control group, while the other treatments were not significantly different when compared to control group. Results indicated that dietary C. camphora extract was the most effective prophylactic to S. agalactiae and can be a cost-effective and eco-friendly alternative to antibiotics. According to the results of experiment III, the diet supplemented with C. papaya fed for a period of 20 weeks at a dose of 2 g/kg was significantly (P≤ 0.05) reduced the GSI of males and females of Nile tilapia, while diet supplemented with 0.5 and 1 g/kg were not affected significantly (P≥ 0.05) the GSI of fish compared to control group. However, the diets supplemented with C. papaya 1 and 2 g/kg fed for 20 weeks improved significantly (P≤ 0.01) the growth performance of Nile tilapia. In addition, the results revealed that, the diet supplemented with different doses of C. papaya extracts (0.5, 1 and 2 g/kg) fed for 3 weeks were not affected significantly (P≥ 0.05) the sexual maturity and growth performance of the Nile tilapia. Overall, it could be concluded that C. papaya extracts at 2 g/kg dose is the best among the screened used herbal extracts and most effective on delaying sexual maturity and enhancing growth performance of Nile tilapia. It can be recommended as a natural reproductive inhibitor and feed additive for Nile tilapia. While dietary supplemented with C. camphora extract, was the most effective prophylactic herbal extract against S. agalactiae.